Modified test assembly for water tree study on polymeric insulating materials - Che Mohamad Shukri, Che Nuru Saniyyati (2014)
Water tree is a process that causes degradation of insulation performance and ageing of Cross-Linked Polyethylene (XLPE) underground cables. It is known as one of the major causes of premature ageing and failure of polymeric cables. Previous research has shown that there are different effects of ageing time on water tree growth in different types of polymeric insulating materials where nickel and platinum have been used as electrodes and were found to cause corrosion and reduce efficiency. Thus, in this research, a modified test assembly using tungsten needle as an electrode to avoid corrosion and increase efficiency was introduced. This research investigated the effects of ageing time on water tree growth in two different types of polymeric sample namely (XLPE) and Low-Density Polyethylene (LDPE) under high voltage stress. Using computational simulation, the effect of voltage application and angle of tip radius against electric field using COMSOL 4.2a was studied. In this study, the polymeric samples were prepared using a new method known as “leaf-like” specimen method. The experiment was based on BS IEC 61956 2001, “Methods of test for the evaluation of water treeing in insulating materials” and BS EN 60243-1 : 1998, “Electrical strength of insulating materials-Test methods”. Samples were exposed to high voltage injection for 150 hours and 470 hours. The simulation results show that when voltage application increases, the electric field will increase. Besides that, a lower angle of tip radius in polymeric sample, will result in higher electric field being produced. Experimental results show that water tree growth is proportional to ageing time of the two polymeric samples. However, XLPE has better water treeing resistance than LDPE because the average length of water tree growth for LDPE is higher as compared to XLPE. This study has shown that ageing time as the cause of water tree growth that causes degradation in insulation performance has different effects on different types of polymers.